2001
DOI: 10.1210/endo.142.12.8557
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endogenous Opioid Peptides in Mediating Progesterone-Induced Disruption of the Activation and Transmission Stages of the GnRH Surge Induction Process

Abstract: How progesterone blocks the E2-induced GnRH surge in females is not known. In this study we assessed whether the endogenous opioid peptides (EOPs) that mediate progesterone negative feedback on pulsatile GnRH secretion also mediate the blockade of the GnRH surge. We treated ovariectomized ewes with physiological levels of E2 and progesterone to stimulate and block the GnRH surge, respectively, using LH secretion as an index of GnRH release. A pilot study confirmed that blocking opioidergic neurotransmission wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…10, top panel), after a delay corresponding to the duration of progesterone administration. A similar tendency of delayed surge onsets has been observed experimentally after progesterone treatments that were inefficient to block the surge (21). Because the experiments described in the literature have been conducted in induced (artificial) follicular phases, where the neurosecretory events are condensed compared to physiological follicular phases, the delays mentioned in our numerical experiments are greater than the corresponding ones in the biological experiments.…”
Section: Numerical Progesterone Blockadesupporting
confidence: 74%
See 1 more Smart Citation
“…10, top panel), after a delay corresponding to the duration of progesterone administration. A similar tendency of delayed surge onsets has been observed experimentally after progesterone treatments that were inefficient to block the surge (21). Because the experiments described in the literature have been conducted in induced (artificial) follicular phases, where the neurosecretory events are condensed compared to physiological follicular phases, the delays mentioned in our numerical experiments are greater than the corresponding ones in the biological experiments.…”
Section: Numerical Progesterone Blockadesupporting
confidence: 74%
“…A series of studies (19)(20)(21)(22) have been dedicated to investigating experimental blockade of the oestradiol-induced GnRH surge by progesterone. It was first shown that progesterone acts centrally, on the hypothalamic level.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…Endogenous opioid peptides are important regulators of the GnRH system, controlling both the preovulatory surge (17) and pulsatile secretion (18) of GnRH. OFQ has been shown to inhibit forskolin-induced GnRH secretion in a dose-dependent manner from rat hypothalamic fragments (19).…”
mentioning
confidence: 99%
“…This includes the regulation of hormone release in the hypothalamic-pituitary axis (Goodman et al, 1995;Richter et al, 2001;Pimpinelli et al, 2006;Brunton and Russell, 2008) and placenta (Belisle et al, 1988;Ahmed et al, 1989;Cemerikic et al, 1991), in pain modulation during pregnancy and labor (Dabo et al, 2010), and in the regulation of uterine motility (Zhu and Pintar, 1998). We characterised the effect of a met-enkephalin analog DAMEA on spontaneous human myometrial contractility.…”
Section: Discussionmentioning
confidence: 99%